DETEKSI Staphylococcus aureus dan Salmonella PADA JAJANAN SIRUP - Ririn Puspadewi; Putranti Adirestuti; Afif Abdulbasith (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
Microbial on food are caused by various factors such as nutrients, water, and temperature. If total amount of microbes increase it would damage food and if it ingested could affect grastrointestinal track. Snack, especially unregistered snack such as syrup in school is one of important problem to concerned. The purpose of this study is to detect the present of Staphylococcus aureus and Salmonella in syrup in four elementary schools in Cimahi. Detection of Staphylococcus aureus is done using BPA medium, while detection of Salmonella is using Indol test, methyl red test, Voges Proskauer test, Citrate test and Gram staining. The result shows that the syrup from the elementary school contains Staphylococcus aureus but not all of samples of syrup give positive result of Salmonella. Based on the requirements which in set in SNI that microbes in syrup should not be contain to Staphylococcus aureus is negative/ml and Salmonella is negative/25 ml, then syrup that sold in all four elementary schooldi not qualified.